Assessment of Entrepreneurial Behavior Skills among Small Farmers: An Exploratory Study - Agbolosoo, John Atsu; Anaman, Richmond (SEISENSE (PRIVATE) LIMITED, 2021)
Aim - The study assessed the entrepreneurial behavior skills of smallholder potato farmers in Nakuru County, Kenya. Methodology - A structured questionnaire was used to collect data. Data were collected from a total of 267 respondents using multistage sampling techniques. The principal component analysis was used to check the reliability and construct variability of entrepreneurial behavior skills. An entrepreneurial behavior index was generated to measure the behavior skills of smallholder potato farmers. Findings - The results show that most smallholder potato farmers had a medium level of risk-taking ability, proactiveness behavior, innovativeness behavior, information-seeking behavior, cosmopoliteness behavior, and decision-making ability. The study concluded that this medium level of entrepreneurial behavior skills made smallholder potato farmers unable to perceive potato farming as a profitable and viable agribusiness venture. Originality - The study recommends that entrepreneurial training with practical demonstration and effective communication skills should be used as an approach to empower and promote the development of entrepreneurial behavior qualities among smallholder potato farmers.